The Cadomian Orogeny and the opening of the Rheic Ocean: The diacrony of - Linnemann, Ulf (2008)
Cadomian orogenic processes and their continuum to the opening of the Rheic Ocean were modeled by making use of new LA-ICP-MS U–Pb ages from detrital zircons of sedimentary rocks of Late Neoproterozoic (Ediacaran) and Cambro-Ordovician sediments of the Ossa-Morena Zone (Iberian Massif) compared with those from the Saxo-Thuringian Zones (Bohemian Massif). Presented data constrain a diachrony of Cadomian and related geotectonic processes along the northern realm of the Gondwana Supercontinent. Early stage of Cadomian evolution is characterized by a continental magmatic arc at the periphery of the West African Craton and a related back-arc basin opened at c. 590 to 570 Ma. Diacronic arc–continent collision was caused by oblique vector of subduction and started first in the East of Peri-Gondwana at c. 560–570 Ma and resulted at c. 543 Ma in the formation of a short-lived Cadomian retro-arc basin in the Saxo-Thuringian Zone. In contrast, more to the West in the Ossa-Morena Zone, the Cadomian back-arc basin was longer active, at least until c. 545 Ma. In that region, final magmatic pulse of the Cadomian magmatic arc at c. 550 Ma is documented by new zircon data. Closure of the Cadomian back-arc basin and arc–continent collision in the Ossa-Morena Zone occurred between c. 545 Ma and the overall onset of Cambrian plutonism at c. 540 Ma. A mid-oceanic ridge was subducted underneath the Cadomian orogen accompanied by slab break-off of the subducted oceanic plate. Oblique incision of the oceanic ridge into the continent caused the formation of rift basins during the Lower to Middle Cambrian (c. 530–500 Ma). This process continued and finally caused the opening of the Rheic Ocean documented by thick Lower Ordovician siliciclastic sediments and a final magmatic event at c. 490–485 Ma. Opening of the Cambrian rift basin and of the Rheic Ocean again was diachronic and started from the West of Peri-Gondwana and expanded eastward.